Zika Virus: An Emergence of a New Arbovirus - Yadav, Sankalp (J Clin Diagn Res, 2016)
The world is facing a new pandemic in progress due to a mosquito-borne flavivirus popularly known as Zika virus. The emergence of this new virus is really alarming with the sudden increment in the cases of microcephaly reported from Brazil. The findings attributing the involvement of Zika virus as the reason for congenital deformations in the babies born in afflicted areas have really shocked the world. The present knowledge about this virus is very limited and in the absence of further studies the precautions seems to be the best way of protection from this virus. The present article is a short review about this new virus.